Dependence of membrane morphology and performance on preparation conditions: the shear rate effect in membrane casting - Kusworo, Tutuk Djoko; Ismail, Ahmad Fauzi; Mustafa, Azeman; Matsuura, T. (Elsevier B.V., 2008)
This study focuses on the effect of shear rates on molecular orientation and gas separation performance of polyimide/polyethersulfone (PI/PES)-zeolite 4A mixed matrix membrane. PI/PES-zeolite 4A mixed matrix membrane was prepared by a dry/wet phase inversion technique using a pneumatically controlled flat sheet membrane casting machine. Membranes were casted at different shear rates, and consequently its effects on molecular orientation and gas performance were studied. At low shear rates, the permeances of O2 and N2 decreased, while their selectivities increased with an increase in shear rates. In low shear rate region, the decrease in permeance or increase in selectivity with increasing shear arose from the better molecular orientation and chain-packing induced by shear. On the contrary, in the high shear region, the increase in permeance or decrease in selectivity was believed to be attributed by porous skins and fracture. Surprisingly, it was found that in high shear region the deterioration of molecular orientation had been detected and appeared to be contradicted from the previous studies. Based on the experimental results, there may have existed an optimum shear rate to yield optimal membrane morphology for gas separation. The selectivity of 581 sâˆ’1 sheared membrane had been further improved to 5.92 at 100 Â°C curing temperature and 72 h curing time